DEVELOPMENT OF THE METHODOLOGY OF ANALYZING THE FINANCIAL SECURITY OF THE ENTERPRISE - KHRUSHCH, Nila; KHRUSHCH, Vitalii; PAIONK, Oksana; YAREMCHUK, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The study focuses on the critical importance of the issues of ensuring the financial security of economic entities in the current conditions. In turn, this requires the formation of full-fledged information and analytical support, based on qualitative methods of analyzing the financial security of the primary sector of the economy. The purpose of the research is to generalize the existing methodological approaches and further develop the methodology for analyzing the financial security of the enterprise. It is summarized that the key aspects of analyzing the financial security of enterprises are the diagnosis of threats in the field of finance, the monitoring of factors characterizing the stability of the financial and economic state of the enterprise in the short and medium term, the analysis of indicators (indicators) for assessing the level of financial security, and the determination of their limit and threshold values. Their characteristics are given. It is indicated that a particularly important place in the methodical provision of analyzing the financial security of an enterprise is given to predicting financial risks and taking into account both the probability and the level of their negative impact. The main provisions of the author’s methodical approach to analyzing the financial security of economic entities have been developed and presented. The scientific novelty of the research results lies in deepening the methodology of analyzing the financial security of the enterprise by developing the author’s methodical approach. The applied value of the research results is that the analytical centers of enterprises receive better methodological support for the identification of financial risks and threats, a more detailed analysis of the state of financial security and the justification of better management decisions in the field of ensuring the financial and economic state of the enterprise.